Models of two big economies and a monetary union (Economic and Political Thought, 2016)
The analysis of open economy in a short term both in the theory of economicsand education has a very strong foundation in the IS-LM-BP Model,which has limitations that have a fundamental practical importance in thecontext of the European integration. Namely, the model does not allow fora monetary union case study. Because of that, it is worth looking closely atthe analysis of the domestic and foreign economy, which is possible within themodel of the two economies. Broadening the perspective onto two entitiesallows not only for observation of the effects of macroeconomic shocks inthe two economies but also for a detailed analysis of mechanisms responsiblefor the transmission of shocks from one country to another. In addition, theapproach based on two economies let the author develop a completely newmodel of two countries functioning in the conditions of a monetary union,which allows for an analysis of shock transmission that is not possible in caseof a model with a fixed currency exchange rate. The presented model of twoeconomies functioning in the conditions of a monetary union also has educationaladvantages connected with its simplicity in comparison with a modelof two big economies. The analysis of the models of two big economies withflexible currency exchange rate and economies in a monetary union showsconsiderable differences in the functioning of the two group types. The differencesconcern not only the effects of macroeconomic shocks (both real andnominal) in the analysed countries but also the way of transmitting shocksfrom one country to another.